Developmental changes in burnout perceptions among student-athletes: An achievement goal perspective - Ingrell, J.; Johnson, U.; Ivarsson, A. (International Journal of Sport and Exercise Psychology, 2019)
This study examined (a) the developmental trajectories of student-athlete burnout perceptions and (b) the within-person relationship between achievement goals and burnout perceptions. A three-year and six-wave longitudinal study was conducted with 78 student-athletes (30 young women and 48 young men, Mage at T1 = 12.7 years, SD = 0.44), attending a sport compulsory school. The Athlete Burnout Questionnaire and the Task and Ego Orientation in Sport Questionnaire were used. The results from multilevel growth models revealed that burnout perceptions increased for this age group over the three-year period. Furthermore, task orientation was significantly and negatively related to a reduced sense of accomplishment and sport devaluation. The results from this study underline the advantage of considering developmental processes when studying burnout. Furthermore, by focusing on the within-person effect of achievement goals, this study provides findings that support a motivational approach to the longitudinally study of burnout propensity among young student-athletes. The current study suggests that sport school staff should be aware of their student-athletes` burnout perceptions and that these could change over time. Results also highlights that task-oriented goals might help decrease burnout perceptions, specifically reduced sense of accomplishment and sport devaluation.